2015
DOI: 10.1097/pec.0000000000000141
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Application of Cerebral rSO2 Monitoring During Shunt Tap in Pediatric Ventricular Malfunctioning Shunts

Abstract: Reliable cerebral rSO2 readings before, during, and after shunt tap were demonstrated. Left cerebral rSO2 changes from before to after shunt tap were more predictive for shunt malfunction location than right cerebral rSO2 changes. Observing cerebral rSO2 changes in relationship to shunt tap represents a potential surrogate in measuring cerebral pressures and blood flow changes after cerebral spinal fluid drainage. Significantly greater cerebral rSO2 changes occur for distal malfunction versus proximal malfunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(46 citation statements)
references
References 23 publications
4
42
0
Order By: Relevance
“…Therefore, rcSO 2 does not provide an indicator of oxygen delivery and instead provides information regarding the balance between regional oxygen supply and demand (4). Recent studies have suggested that pediatric patients may benefit from rcSO 2 monitoring during surgery (5)(6)(7)(8)(9). The use of rcSO 2 is increasing, but the routine use of rcSO 2 as a standard-of-care monitor is still not recommended at present.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, rcSO 2 does not provide an indicator of oxygen delivery and instead provides information regarding the balance between regional oxygen supply and demand (4). Recent studies have suggested that pediatric patients may benefit from rcSO 2 monitoring during surgery (5)(6)(7)(8)(9). The use of rcSO 2 is increasing, but the routine use of rcSO 2 as a standard-of-care monitor is still not recommended at present.…”
Section: Introductionmentioning
confidence: 99%
“…This small, preliminary SCEDKA cerebral oximetry with 3% HTS infusion study demonstrated that initial bihemispheric r c SO 2 readings were greater than 90% respectively signifying initial bihemispheric altered cerebral physiology in comparison with Robert's nonhemispheric cerebral oximetry DKA study with SCEDKA r c SO 2 readings above 90%. 10,11 For the 3% HTS SCEDKA patients, their initial and pre-3% HTS infusion bihemispheric r c SO 2 readings were severely elevated (>90%) in comparison with non-SCEDKA DKA patients and correlated to the SCEDKA patients' altered altered mental status and lower GCS indicating clinically evident cerebral edema. In these patients with severe altered AMS and lower GCS, these severely elevated bihemispheric r c SO 2 readings indicated significant altered bilateral cerebral physiology in comparison with non-SCEDKA DKA patients.…”
Section: Discussionmentioning
confidence: 96%
“…[6][7][8][9][10][11] In this preliminary study, all SCEDKA patients had consistently high initial near infrared spectroscopy readings, post-3% HTS infusions a sharp decline in bihemispheric r c SO 2 readings and a short transient below 60% bihemispheric r c SO 2 readings, and then a rebound to normal bihemispheric r c SO 2 readings. [6][7][8][9][10][11][12][13][14][15][16][17][18] These bihemispheric r c SO 2 reading changes also correlated to the changes in GCS. From this study, it was demonstrated that there were no deleterious effects on the electrolytes or mental status from the 3% HTS infusions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our results expand on previous studies of optical neuromonitoring in this population, which commonly relied on detection of diminished cerebral oxygenation using nearinfrared spectroscopy. [26][27][28][29][30] Whereas cerebral oxygenation has been associated with ventricular dilation 30 and has been demonstrated to improve after CSF diversion, [26][27][28][29] nearinfrared spectroscopy measurements have limited reproducibility and reliability. 31,32 FD-DOS uses a more quantitative measurement of StO 2 that accounts for tissue scattering.…”
Section: Discussionmentioning
confidence: 99%